Writing Anxiety among Indonesian EFL College Students: Levels, Causes, and Coping Strategies - Delvi Wahyuni, Delvi Wahyuni; Witri Oktavia, Witri Oktavia; Leni Marlina, Leni Marlina (Bina Nusantara University, 2019)
This research aimed at investigating foreign language writing anxiety experienced by Indonesian EFL learners studying at Universitas Negeri Padang. The numbers of participants involved in this survey were 132 students comprising of sophomores, junior, and senior students. This research employed three research instruments: Second Language Writing Anxiety Inventory (SLWAI) to collect data on students’ levels of writing anxiety; Causes of Writing Anxiety Inventory (CWAI) to gauge information about sources of students’ writing anxiety; typologies of tactics to cope with writing anxiety. The result of this research reveals that the level of students’ writing anxiety is moderate. In addition, no significant relationship between students’ writing anxiety level and their academic level is revealed suggesting moderately anxious students outnumbering those with high and low writing anxiety at any academic level. In addition, the sources of students’ writing anxiety are problems with topic choice, linguistic difficulties, and lack of writing practice. The coping strategies used by students to overcome writing anxiety are preparation, positive thinking, relaxation, peer-seeking, and resignation (most-frequent to least frequent respectively).